Cardioprotection Generated by Aerobic Exercise Training is Not Related to the Proliferation of Cardiomyocytes and Angiotensin-(1-7) Levels in the Hearts of Rats with Supravalvar Aortic Stenosis - Augusto Ferreira Mota, Gustavo [UNESP]; Luiz Borges de Souza, Sérgio [UNESP]; Loureiro da Silva, Vitor [UNESP]; Gatto, Mariana [UNESP]; Henrique Salomé de Campos, Dijon [UNESP]; Grippa Sant’Ana, Paula [UNESP]; Vileigas, Danielle Fernandes [UNESP]; Padovani, Carlos Roberto [UNESP]; Casarini, Dulce Elena; Menezes de Oliveira, Edilamar; Garcia Zanati Bazan, Silméia [UNESP]; Fernandes, Tiago; et al. (Cell Physiol Biochem Press, 2020)
Background/Aims: The beneficial effect of aerobic exercise training (ET) on cardiac remodeling caused by supravalvar aortic stenosis (AS) has been demonstrated in experimental studies; however, the mechanisms responsible for improving cardiac function are not entirely understood. We evaluated whether ET-generated cardioprotection in pressure-overloaded rats is dependent on cardiomyocyte proliferation, increased angiotensin-(1-7) (Ang-1-7) levels, and its receptor in the myocardium. Methods: Eighteen weeks after ascending AS surgery, Wistar rats were randomly assigned to four groups: sedentary control (C-Sed), exercised control (C-Ex), sedentary aortic stenosis (AS-Sed) and exercised aortic stenosis (AS-Ex) groups. The moderate treadmill exercise protocol was performed for ten weeks. The functional capacity was assessed by treadmill exercise testing. Cardiac structure and function were evaluated by echo.
Keywords: Cardiac dysfunction; Cardiac remodeling; Cell cycle; Physical training; Renin-angiotensin system